Development of millet-acid whey formulations with nutritional, microbiological, and sensory characterization - Malik, Sargun; Mustapha, Azlin; Krishnaswamy, Kiruba (Frontiers in Sustainable Food Systems, 2023)
Introduction Disposal of the acid whey waste stream is one of the major challenges faced by the Greek yogurt industry. However, based on its physicochemical characteristics and composition analysis, it has huge potential in the health industry. Likewise, millets are highly nutritive and health benefitting ancient grains. Combining acid whey and millet matrix can help in solving the problem of both food losses and food security. Hence, the objective of the study is to analyze the enhancement or degradation of the nutrition profile when acid whey is combined with millet matrix using spray-drying technology. Method The methodology of the study includes composition analysis and functional characterization based on antioxidant properties, microbial analysis, and sensory evaluation. Results and discussion The results showed that there was enhancement of functional properties of the millet-acid whey formulation matrix specifically in terms of polyphenolic compounds, lactose content, and mineral content. Overall, the study aims to provide an alternative method for the utilization and consumption of acid whey that is currently being mishandled and considered as waste by the Greek yogurt manufacturing companies.